2008
DOI: 10.1001/archsurg.143.10.978
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Ligation as an Efficient Method of Increasing the Future Liver Remnant Volume in the Surgical Treatment of Colorectal Metastases

Abstract: To compare the volumetric increase of segments 2 and 3, segment 4, and the caudate lobe after portal vein ligation (PVL) and portal vein embolization (PVE). The small size of the remnant liver and chemotherapyinduced liver injury increase the risk of postoperative hepatic insufficiency after major hepatic resection for colorectal liver metastases. Portal vein ligation has been suggested to be less effective than embolization in inducing hypertrophy of the remnant liver. Design, Setting, and Patients: We retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 25 publications
3
86
0
13
Order By: Relevance
“…5 The current systematic review showed hypertrophy of 26-47% at time intervals of from 44 days to 9 months after unilobar SIRT with Y90. Thus while the degree of growth achieved is comparable to that achieved with PVE alone, and superior to that achieved after PVE + TACE, the kinetics of hypertrophy after SIRT are likely to be different from PVE.…”
Section: Other Findingsmentioning
confidence: 55%
“…5 The current systematic review showed hypertrophy of 26-47% at time intervals of from 44 days to 9 months after unilobar SIRT with Y90. Thus while the degree of growth achieved is comparable to that achieved with PVE alone, and superior to that achieved after PVE + TACE, the kinetics of hypertrophy after SIRT are likely to be different from PVE.…”
Section: Other Findingsmentioning
confidence: 55%
“…Consequently, in recent literature, a residual volume, the "standardized FLR" (sFLR) of 25-30% has been described as the benchmark in patients with normal liver function 7 and volumes of at least 40% in patients with parenchymal liver disease. 8,9 Three methods to enlarge FLR are possible in this situation before ERH: (1) surgical right-sided portal vein ligation (PVL), 10,11 (2) portal vein embolization (PVE) as an interventional approach used by various centres [12][13][14] and (3) the surgical approach of "associating liver partition with PVL for staged hepatectomy". [15][16][17] However, as hypertrophy following PVE is necessary but highly variable, we retrospectively analyzed data from our patient cohort for differences in those with good hypertrophy (increase to .25% of the sFLR) and those with a less beneficial increase in size of sFLR.…”
Section: Introductionmentioning
confidence: 99%
“…One very important limiting factor for performing major liver resections is the remaining liver volume, referred to as future liver remnant. Postoperative liver failure consequent to insufficiency of remnant liver is a feared complication in patients who underwent extensive liver resections 2,7 . The estimated future liver remnant volume to prevent postoperative liver failure should be at least 25% of total liver volume in healthy livers.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated future liver remnant volume to prevent postoperative liver failure should be at least 25% of total liver volume in healthy livers. For patients with hepatic dysfunction or earlier liver injury due to chemotherapy, a higher future liver remnant (approximately 40%) is recommended 2,7 . Some strategies have been developed to increase resectability in patients undergoing major hepatic resection.…”
Section: Introductionmentioning
confidence: 99%